Spotlight on Cemiplimab-rwlc in the Treatment of Non-Small Cell Lung Cancer (NSCLC): Focus on Patient Selection and Considerations - Ahn J; Nagasaka M (Cancer Management and Research, 2023)
Jeffrey Ahn,1 Misako Nagasaka1,2 1Department of Medicine, University of California Irvine School of Medicine, Chao Family Comprehensive Cancer Center, Orange, CA, USA; 2St. Marianna University School of Medicine, Kawasaki, JapanCorrespondence: Misako Nagasaka, Department of Medicine, University of California Irvine School of Medicine, Chao Family Comprehensive Cancer Center, 101 The City Drive South, Orange, CA, 92868, USA, Email nagasakm@hs.uci.eduAbstract: In metastatic non-small cell lung cancer (NSCLC), tumors that do not harbor driver mutations in EGFR or gene fusions in ALK and ROS, PD-1 and PD-L1 inhibitors have become a cornerstone in first line treatment, either as monotherapy or in combination with chemotherapy. This paper reviews cemiplimab-rwlc, the third PD-1/L1 inhibitor to be approved in the setting for first line treatment in NSCLC, as monotherapy or in combination therapy with chemotherapy, to provide a perspective on the subtle differences in patient population for the cemiplimab studies and consideration of its primary and subgroup results in the context of first line therapies for NSCLC.Keywords: immunotherapy, monotherapy, combination chemotherapy, PD-L1